Shadow Teacher Training for Autistic Children at Raudhatul Athfal Ashabul Kahfi, Parepare City - Tadzkirah; Novita Ashari; Tri Ayu Lestari Natsir; Nadia; Muftihatul Khaeriyah Syukri (PT FORMOSA CENDEKIA GLOBAL, 2022)
Shadow teacher training for autistic children aims to increase the knowledge and abilities of educators, especially Kindergarten teachers/Raudhatul Athfal in developing shadow teacher learning tools for autistic children. This training was held on November 5, 2022 for four days and assistance was provided for making individual learning programs. The initial stage of the training reviews the importance of accompanying teachers, because it will motivate autistic children to be more focused and programmed in learning activities. The second stage of the training is to explain and describe the main tasks and responsibilities of the accompanying teacher. The third stage of the training is the practice of how to shadow teacher therapy for autistic children. The final stage of the training is evaluation, this activity is intended as an indicator of the success of the training. The results of this training found that core teachers were increasingly skilled in handling and able to treat autistic children and know the responsibilities of the shadow teacher.